First isolation of Borrelia lusitaniae DNA from green lizards (Lacerta viridis) and Ixodes ricinus ticks in the Czech Republic - Musilová, Lucie; Kybicová, Kateřina; Fialová, Alena; Richtrová, Eva; Kulma, Martin (Ticks and tick-borne diseases, 2022)
This study aimed to reveal whether green lizards (Lacerta viridis), common hosts of tick larvae and nymphs, might be involved in the transmission cycle of Borrelia burgdorferi sensu lato in the Czech Republic. Green lizards were sampled in two areas at the Tiché Údolí Nature Reserve (site A: 50.1482 N, 14.3669E; site B: 50.1476 N, 14.3745 E), Central Bohemian Region, Czech Republic. The skin biopsy specimens and attached ticks (if any) were collected from 52 captured lizards. Also, questing ticks from both areas were collected by flagging. The touchdown polymerase chain reaction and gel electrophoresis revealed Borrelia lusitaniae in three lizard tissue samples. Most lizards (19/30, 63%) had at least one Borrelia positive tick. Borrelia lusitaniae formed 92% (34/37) and 59% (17/29) of all borreliae detected in larvae and nymphs, respectively. Borrelia lusitaniae (6/10, 60%) was also the major pathogen in questing nymphs from site B. At site A, 13% (2/16) of questing nymphs were positive for B. lusitaniae. Based on our data, it can be assumed that B. lusitaniae is a common pathogen at lizard sites in the Czech Republic, and further research to prove this hypothesis is therefore highly recommended. As lizards often inhabit urban areas, the data presented may also contribute to raising awareness of the possible spread and risk of Borrelia infection.
Keywords: DNA; Nymph; Animals; Czech Republic; Borrelia burgdorferi Group; Spirochaetales; klíště; Lizards; Lyme Disease; ještěři; nymfa; lymeská nemoc; Borrelia burgdorferi komplex; Česká republika; zvířata; Ixodes